2018
DOI: 10.1158/0008-5472.can-17-3841
|View full text |Cite|
|
Sign up to set email alerts
|

Hypoxic Tumor-Derived Exosomal miR-301a Mediates M2 Macrophage Polarization via PTEN/PI3Kγ to Promote Pancreatic Cancer Metastasis

Abstract: Exosomes are emerging as important mediators of the cross-talk between tumor cells and the microenvironment. However, the mechanisms by which exosomes modulate tumor development under hypoxia in pancreatic cancer remain largely unknown. Here, we found that hypoxic exosomes derived from pancreatic cancer cells activate macrophages to the M2 phenotype in a HIF1a or HIF2a-dependent manner, which then facilitates the migration, invasion, and epithelial-mesenchymal transition of pancreatic cancer cells. Given that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
459
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 570 publications
(474 citation statements)
references
References 47 publications
(64 reference statements)
12
459
1
2
Order By: Relevance
“…Interestingly, a slight increase in size of SEV was observed under moderate hypoxia (1.0% O 2 ) in both the cell lines. 33 In other studies, EVs derived from a variety of cancer cells grown under hypoxia are shown to contain miR-21, 45,46 a downstream target of HIF-1α, which plays important roles in hypoxic tumor cell survival. However, an increased release of EV under hypoxia counters this argument.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Interestingly, a slight increase in size of SEV was observed under moderate hypoxia (1.0% O 2 ) in both the cell lines. 33 In other studies, EVs derived from a variety of cancer cells grown under hypoxia are shown to contain miR-21, 45,46 a downstream target of HIF-1α, which plays important roles in hypoxic tumor cell survival. However, an increased release of EV under hypoxia counters this argument.…”
Section: Discussionmentioning
confidence: 94%
“…18,33 Furthermore, it has also been demonstrated that their biogenesis and shedding can be influenced by extracellular stimuli, which holds broader functional significance. Although initially believed to serve as trash bags to get rid of unwanted cellular material, EVs are now established as functional entities that are capable of altering the properties of the recipient cells through transfer of bioactive cargo.…”
Section: Discussionmentioning
confidence: 99%
“…The dysregulation of miRNA activity can lead to F I G U R E 4 Size of the exosomes in the serum of SCAD patients, confirmed using the NanoSight instrument. SCAD, stable coronary artery disease immune responses in severe asthma (fibroblast-derived exosomes promote epithelial cell proliferation through the TGF-beta2 signalling pathway), 22 pancreatic cancer metastasis (exosomal miR-301a mediates M2 macrophage polarization via PTEN/PI3Kγ), 23 non-small-cell lung cancer (exosomal miR-451a), 24 acute coronary syndrome (exosomal miR-208a), 25 and so on. Compared with plasma or serum miRNAs, exosomal miRNAs are accurate, sensitive, and specific.…”
Section: Discussionmentioning
confidence: 99%
“…Exosome and its components coactivate intercellular cross‐talk between metastatic malignancy and normal tissue under environmental low oxygen tension. Wang et al . purposed that anoxic pancreatic tumor cells recruited exosomal miR‐301a‐3p to trigger the M2 polarization of macrophages through the PTEN/PI3Kγ axis, led to a greater invasive depth of cancer cells as well as EMT (Table ).…”
Section: Exosome and Tumor Developmentmentioning
confidence: 99%
“…Exosome and its components coactivate intercellular cross-talk between metastatic malignancy and normal tissue under environmental low oxygen tension. Wang et al 31 purposed that anoxic pancreatic tumor cells recruited exosomal miR-301a-3p to trigger the M2 polarization of macrophages through the PTEN/PI3Kγ axis, led to a greater invasive depth of cancer cells as well as EMT (Table 1). And Xue et al 32 isolated and identified hypoxic bladder cancer cell-derived exosomes, and their result showed that oncogenic lncRNA-UCA1-enriched exosomes remodeled tumor microenvironment to facilitate tumor growth (Table 1).…”
Section: Cancer Metastasismentioning
confidence: 99%